Chinese Neonatal Follow-Up Network: a national protocol for follow-up assessment and collaborative research to improve developmental outcomes of high-risk preterm infants - Qi Zhou; Shoo K Lee; Long Li; Wenhao Zhou; Yun Cao; Nurya Erejep; Wenlong Xiu; Jingyun Shi; Rui Cheng (BMJ Open)
Introduction The objective of the Chinese Neonatal Follow-Up Network (CHNFUN) is to establish a standardised follow-up protocol for the assessment of high-risk preterm infants, and collaborative research aimed at improving early intervention and neurodevelopmental outcomes for preterm infants with gestational age less than 32 weeks in China. The CHNFUN is the first national neonatal follow-up network and has the largest geographically representative cohort from neonatal intensive care units (NICUs) in China.Methods and analysis A survey of neonatal follow-up clinics participating in CHNFUN was used to inform the development of a standardised protocol for the assessment of high-risk preterm infants in China. Training in the use of assessment tools and data collection was provided to all participating centres. Individual-level neurodevelopmental outcomes data from participating neonatal follow-up clinics will be collected at corrected age, 40 weeks, 3–4 months, 12 months, 18–24 months, 3 years and 6 years of age, using a unique database developed by the CHNFUN and linked to NICU outcomes data in the CHNN Database. Data will be prospectively collected on an ongoing basis from all surviving infants born at <32 weeks’ gestation or <1500 g birth weight and discharged from 34 participating NICUs from 1 June 2023. Infant neurodevelopmental outcomes and interinstitutional variations in outcomes will be examined and used to inform quality improvement measures aimed at improving outcomes, development and evaluation of early intervention programmes and other collaborative research, including clinical trials.Ethics and dissemination This study was approved by the ethics review board of Children’s Hospital of Fudan University (#CHFU 2022-112), which was recognised by all participating hospitals. Waiver of consent was granted at all sites. Only non-identifiable patient-level data will be transmitted, and only aggregate data will be reported in CHNFUN reports and publications.